Modernisasi Sistem Pendidikan di Pondok Pesantren Hidayatullah Nias - Masliana Mendrofa; Nurjanah Nurjanah; Moh. Ali Hafid (Halaqa: Journal of Islamic Education, 2026)
The significance of this research is rooted in the digital literacy gap phenomenon in pesantren located in frontier, outermost, and underdeveloped regions, such as the Nias Islands. This study aims to describe the educational modernization process at Pondok Pesantren Hidayatullah Nias, analyze the determinant factors, and formulate an integration model of traditional values and digital innovation. The research method employs a qualitative case study approach with observation, in-depth interviews, and documentation techniques. The results indicate a systematic transformation from sorogan-bandongan methods to tiered classical systems, the integration of independent curricula with national standards, and the initiation of data-based administration. The novelty of this research lies in the modeling of technological adaptation within a minority pesantren ecosystem in an archipelago region with limited infrastructure access. Policy implications from these findings emphasize the need for government-led digital infrastructure schemes specifically for archipelago-based pesantren to minimize digital exclusion. Realigning adaptive leadership strategies remains the key to maintaining scientific lineage amidst modernization currents that are increasingly unavoidable.